SEASONAL VARIATIONS OF IONOSPHERIC LAYERPARAMETERS DURING THE PERIOD OFMAXIMUM SOLAR ACTIVITY - Kravetz, R. O.; Galanin, V. V. (Одеські астрономічні публікації, 2014)
Critical frequencies of the ionospheric layers were studied using data from the European Digital Upper Atmosphere Server (DIAS) network of real-time ionosondes for 2012-2013. Some particularities of seasonal variations of these parameters were detailed.